A Flipped Classroom-Based Education System for College English Teaching - Haiyan Zhang (International Journal of Emerging Technologies in Learning (iJET), 2019)
The flipped classroom (FC) is a novel teaching mode combining traditional class-room and computer network technology. This paper attempts to design a FC-based education system for college English teaching, which is critical to the quali-ty of English teaching in colleges. In our research, a college English education system is established based on SQL server and FC. The architecture and func-tional modules of the system were discussed in details. Specifically, the system architecture was created based on the browser/server (B/S) structure, the data management was realized by SQL server 2008, and the system functions were designed and achieved by JavaServer Pages (JSP). The proposed system was tested in an actual application. The results confirm that the system can meet the teaching demand, arouse the students’ interest in learning and improve the effect of English teaching.